Analysis of the Cultured Microbiome of Fertilization-Stage Maize Silks (Styles) Reveals Taxonomic Relationships Across North American Maize Genotypes and Heterotic Groups - Michelle E. H. Thompson; Anuja Shrestha; Eman M. Khalaf; Jeffrey Rinne; Victor Limay-Rios; Lana M. Reid; Manish N. Raizada (Bacteria)
The style is the female reproductive channel in flowers, receiving pollen and transmitting male gametes through elongating pollen tubes to the ovules during fertilization. In maize/corn, the styles are known as silks. Fertilization-stage silks contain diverse bacteria, possibly originating from pollen. Bacteria were cultured and individually sequenced from the tip and base portions of healthy, fertilization-stage silks of 14 North American maize genotypes, resulting in 350 isolates, spanning 48 genera and 221 OTUs. The objective of this study was to taxonomically analyze these bacteria in the context of the maize host tissue and genotype, taking advantage of long-read (V1–V9) 16S Sanger sequencing. The results suggest that the maize genotype and heterotic breeding group may impact the bacterial diversity of healthy, fertilization-stage silks. Some taxa were relatively conserved across maize genotypes and silk tip/base locations, including Pantoea, which may represent part of the core microbiome or form stable, symbiotic relationships with healthy, pollinated silks. We also observed similarities between the silk microbiomes of maize genotypes that were related by plant pedigree; these preliminary results suggest inheritance or the ability of related genotypes to recruit common bacterial taxa. Overall, this study demonstrates that healthy maize silks represent a valuable resource for learning about relationships between plant reproductive microbiomes.